Implementasi Layanan Inklusi di Sekolah: Peran Guru dan Orang Tua dalam Mendukung Perkembangan Anak Berkebutuhan Khusus - Lessy, Nur; Khairunnisa, Atikah (Universitas Pattimura, 2023)
This study aims to explore the implementation of inclusive services in early childhood education settings, specifically at Asy-Syifa Kindergarten in Ambon, with a focus on the role of teachers and parents in supporting the development of children with special needs (CSN). The research employs a descriptive qualitative approach, utilizing observations, in-depth interviews, and documentation as data collection techniques. The findings reveal that teachers at Asy-Syifa Kindergarten design learning activities tailored to children's age and abilities, following established guidelines. At the initial stage, the school provides parenting services for parents of children with special needs to foster synergy between teachers and parents in the educational process. Early detection is conducted to identify the needs and appropriate activities for each child. Additionally, the school recommends therapy as an extra stimulation effort outside school hours to optimize children's development. Assessment is carried out individually, considering each child's abilities and developmental stages. The novelty of this study lies in its emphasis on the importance of intensive collaboration between teachers and parents in ensuring the success of inclusive services, as well as the use of parenting services as a systematic initial strategy. This study recommends enhancing teacher training in early detection of children's special needs and developing specialized parenting modules for parents. The findings contribute to the advancement of social sciences, particularly in inclusive education studies and collaborative practices in early childhood education.